A Survey on Dynamic Resource Allocation in MIMO Heterogeneous Cognitive Radio Networks based on Priority Scheduling - Tamilarasan, S; Kumar, P (International Journal of Computer Sciences and Engineering, 2025)
In cognitive radio networks (CRN) an intelligent spectrum allocation is an immense subjects because of its deficiency of spectrum demand. Resources in CRN would be allocated based on dynamic access methods with respected to sensed radio environment. A principal research trial is that how would be allocated or assigned presented unused spectrum to unlicensed users. In this paper we provide a comprehensive survey of dynamic resource allocation and priority scheduling in MIMO-CRN. The appropriate portion of unmoving recurrence range existing together intellectual radios while amplifying all out transmission capacity utilization what's more, reducing impedance is required for the dynamic range use in MIMO-CRN. The system for established extent segment came to achievement to less range utilization over the entire range. In this paper we presented the different approaches used for dynamic resource allocation and scheduling in heterogeneous MIMO-CRN.